The evaluation of potential global impact of the N501Y mutation in SARS‐COV‐2 positive patients - Komurcu, Selen Zeliha Mart; Artik, Yakup; Cesur, Nevra Pelin; Tanriverdi, Arzu; Erdogan, Derya Cakir; Celik, Sule; Gulec, Elif Yilmaz (Journal of medical virology, 2022)
Rapid and reliable detection of severe acute respiratory syndrome coronavirus 2 mutations are significant to control the contagion and spread rate of the virus. We aimed to evaluate the N501Y mutation rate in randomly chosen positive patients with the polymerase chain reaction (PCR). The evaluation and analysis of the data with a retrospective approach in cases with mutations, in terms of public health, will contribute to the literature on the global pandemic that affects our society. Public health authorities will take the necessary precautions and evaluate the current situation. The N501Y mutation was detected in patients with positive Covid‐19 PCR test results. The positive samples were examined based on the 6‐carboxy‐fluorescein (FAM) channel in reverse transcription PCR (RT‐PCR) quantitation cycle (Cq) values as low Cq (<25), medium Cq (25–32), and high Cq (32–38) groups. In the study, 2757 (19.7%) of 13 972 cases were detected as mutation suspects and 159 (5.8%) of them were found to have mutations. The ages of the cases with mutations ranged from 1 to 88 years (mean age of 40.99 ± 17.55). 49.7% (n = 79) of the cases with mutations were male, and 50.3% (n = 80) were female. When the RT‐PCR‐Cq results were examined, it was seen that it varied between 11.3 and 35.03, with an average of 20.75 ± 3.32.